2022
DOI: 10.1093/immadv/ltac002
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the use of gold nanoparticles conjugated with proinsulin peptide and administered by hollow microneedles as an immunotherapy in type 1 diabetes

Abstract: Antigen-specific immunotherapy is immunomodulatory strategy for autoimmune diseases, such as Type 1 diabetes, in which patients are treated with autoantigens to promote immune tolerance, stop autoimmune beta-cell destruction and prevent permanent dependence on exogenous insulin. In this study, human proinsulin peptide C19-A3 (known for its positive safety profile) was conjugated to ultrasmall gold nanoparticles (GNP), an attractive drug delivery platform due to the potential anti-inflammatory properties of gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
5
24
0
Order By: Relevance
“…Thus, ultrasmall AuNP (< 5 nm) were proposed as delivery carriers of C19-A3, as they can be easily functionalized and present higher uptake by antigen-presenting cells than free peptides. The safety profile of C19-A3-conjugated AuNP intradermally administered via microneedles (three doses at 4-week intervals) was explored in a phase I clinical trial, starting in 2016 [28]. The type 1 diabetes patients tolerated the C19-A3-AuNP doses well, and no signs of systemic hypersensitivity were observed.…”
Section: Clinical Landscape Of Therapeutic Gold Nanoparticlesmentioning
confidence: 99%
“…Thus, ultrasmall AuNP (< 5 nm) were proposed as delivery carriers of C19-A3, as they can be easily functionalized and present higher uptake by antigen-presenting cells than free peptides. The safety profile of C19-A3-conjugated AuNP intradermally administered via microneedles (three doses at 4-week intervals) was explored in a phase I clinical trial, starting in 2016 [28]. The type 1 diabetes patients tolerated the C19-A3-AuNP doses well, and no signs of systemic hypersensitivity were observed.…”
Section: Clinical Landscape Of Therapeutic Gold Nanoparticlesmentioning
confidence: 99%
“…In vitro experiments demonstrated that conjugation of diabetogenic peptides to GNPs facilitated their uptake by antigen presenting cells, particularly Langerhans cells in the skin (1), which have been shown to have tolerogenic properties in some studies (5,6). In the Phase 1 trial, five participants with newly diagnosed T1D received multiple rounds of C19-A3-GNP and we found persistent reactive immune infiltrate at the C19-A3 GNP injection site (2). This provided the unique opportunity to analyse the antigen specificity and phenotype of the tissue infiltrate, rather than the historical approach of peripheral blood analysis, where autoantigen-specific cells are very rare, representing ~0.01% of the total T-cell population (7)(8)(9).…”
Section: Introductionmentioning
confidence: 76%
“…Whilst four participants received 3 doses of C19-A3 GNP, one participant (EEASI-C) received only the first dose due to the decision to halt further drug administration, but they remained in the study and attended all planned visits and assessments. All participants were autoantibody-positive defined by being positive to at least one of GADA, IA-2A, or ZnT8A and possessed HLA-DRB1 * 0401 genotype (2). Two participants had a punch biopsy of the injection sites, 3 months after injection in one (participant EEASI-B) and 7 months after injection in another participant (participant EEASI-A).…”
Section: Study Participantsmentioning
confidence: 99%
“…In addition, clinical trials have tested the coupling of human proinsulin peptide (C19-A3) with AuNPs (C19-A3-AuNPs) for the treatment of type 1 diabetes. In a phase I clinical trial, the safety of intradermal administration of C19-A3-AuNP through microneedles has been explored [93]. Patients with type 1 diabetes have shown good tolerance to C19-A3-AuNPs with no signs of systemic allergy.…”
Section: Acta Materia Medicamentioning
confidence: 99%